2020
DOI: 10.4314/jae.v24i4.11
|View full text |Cite
|
Sign up to set email alerts
|

Food security situations among female headed households in Enugu East Senatorial Zone of Enugu State, Nigeria

Abstract: This study examined the relationship between cultural biases and farmer-herder conflicts in Taraba State, Nigeria. The population was made up of 973 respondents comprising the households of selected farmers and herders in Taraba State. The sample size of210 was selected using purposive sampling procedure. The instrument for data collection was an 18-item questionnaire. One hundred and ninety-five (195) copies of the questionnaire were successfully retrieved and analysed. Mean and standard deviation was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
(11 reference statements)
1
0
0
Order By: Relevance
“…Meanwhile, more extreme experiences such as having no food at all (26.1%), going to sleep hungry (14.7%), or going a whole day without eating (12.8%) were less commonly reported, reflecting a lesser but still concerning degree of acute food deprivation. Consistent with the results, Ozioko et al (2020) found that female-headed households in Nigeria were more food insecure and employed coping strategies such as consuming a few kinds of foods and reducing food consumption altogether. Similarly, in Malawi, Dunga and Dunga (2017) established that due to the low economic status of female-headed households, they employed more coping strategies in response to food shortages as compared to male-headed households.…”
Section: Food Insecurity Experiences Over a 30-day Periodsupporting
confidence: 82%
“…Meanwhile, more extreme experiences such as having no food at all (26.1%), going to sleep hungry (14.7%), or going a whole day without eating (12.8%) were less commonly reported, reflecting a lesser but still concerning degree of acute food deprivation. Consistent with the results, Ozioko et al (2020) found that female-headed households in Nigeria were more food insecure and employed coping strategies such as consuming a few kinds of foods and reducing food consumption altogether. Similarly, in Malawi, Dunga and Dunga (2017) established that due to the low economic status of female-headed households, they employed more coping strategies in response to food shortages as compared to male-headed households.…”
Section: Food Insecurity Experiences Over a 30-day Periodsupporting
confidence: 82%
“…In 2020-2022, 11, 13, and 15 articles were included in this review, respectively. The number of respondents ranged in size from the smallest study (with 72 respondents) [101] to the highest-population study (using secondary data) of 5198 respondents [98].…”
Section: Common Features Of the Reviewed Studiesmentioning
confidence: 99%
“…The southwest had the highest number of FI research studies (45) conducted in the region, while the south-south had the least (9) FI research studies conducted in the region, and only three were reported in Federal Capital Territory (FCT), Abuja (see Figure 3). Furthermore, about 9% (7 articles) of studies in this review employed qualitative methodology [68,76,87,101,103,113,118], while the remaining 91% (72) studies were quantitative in nature. Apart from the survey nature of the studies, some (five studies) incorporated focus group discussion (FGDs) and key informant interviews (KIIs) [59,72,82,83,97].…”
Section: Common Features Of the Reviewed Studiesmentioning
confidence: 99%
See 2 more Smart Citations